The Effect of Green Betel Leaf Decoction on Treating Vaginal Discharge in All Female Students at STIKes Al-Ma’arif Baturaja - Septiani, Eichi (Gayaku Publisher, 2025)
The effect of green betel leaf decoction in treating vaginal discharge in all students experiencing vaginal discharge at STIKes Al-Ma'arif Baturaja in 2023. The purpose of this study was to determine the effect of green betel leaf decoction in treating vaginal discharge in all students experiencing vaginal discharge at STIKes Al-Ma'arif Baturaja in 2023. This research method used a pretest-posttest on 45 respondents experiencing vaginal discharge. After 7 days of observation, the symptoms of vaginal discharge decreased or not for the intervention group. The statistical test used was non-parametric (Wilcoxon test). The significance value of the relationship between maternal age (LBW) was p-value = 0.001 (a <0.005), while the significance value of the relationship between parity and LBW was p-value = 0.001 (a <0.005). Furthermore, there was a relationship between maternal age, and there was no relationship between maternal parity and the incidence of low birth weight babies (LBW).